Pulsatility Produced by the Hemodialysis Roller Pump as Measured by Doppler Ultrasound. Issue 11 (29th April 2015) - Fulker, David; Keshavarzi, Gholamreza; Simmons, Anne; Pugh, Debbie; Barber, Tracie
Abstract Microbubbles have previously been detected in the hemodialysis extracorporeal circuit and can enter the blood vessel leading to potential complications. A potential source of these microbubbles is highly pulsatile flow resulting in cavitation. This study quantified the pulsatility produced by the roller pump throughout the extracorporeal circuit. A Sonosite S‐series ultrasound probe (FUJIFILM Sonosite Inc., Tokyo, Japan) was used on a single patient during normal hemodialysis treatment. The Doppler waveform showed highly pulsatile flow throughout the circuit with the greatest pulse occurring after the pump itself. The velocity pulse after the pump ranged from 57.6 ± 1.74 cm/s to −72 ± 4.13 cm/s. Flow reversal occurred when contact between the forward roller and tubing ended. The amplitude of the pulse was reduced from 129.6 cm/s to 16.25 cm/s and 6.87 cm/s following the dialyzer and venous air trap. This resulted in almost nonpulsatile, continuous flow returning to the patient through the venous needle. These results indicate that the roller pump may be a source of microbubble formation from cavitation due to the highly pulsatile blood flow. The venous air trap was identified as the most effective mechanism in reducing the pulsatility. The inclusion of multiple rollers is also recommended to offer an effective solution in dampening the pulse produced by the pump.